RANCANG BANGUN SISTEM PEMESANAN ONLINE PADA TOKO IKEBANA FLORIST MENGGUNAKAN FRAMEWORK MVC - Jessica Chandra; Marlina; Ahyar Muawwal (STMIK KHARISMA Makassar, 2019)
Responding to increasingly competitive competition in every business, the idea to combine information technology with business has emerged. The purpose of this study is to Design an Online Ordering System at Ikebana Florist Stores Using the MVC Framework. In this study, the author makes an application using the PHP programming language with the Codeigniter framework. This application can manage product data, view products, make ordering and payment transactions and validation. To obtain data and information that support the implementation of this study, observation and interviews were conducted. Implemented using the Atom and MySQL program PhpMyAdmin as a data processor, then tested using the Black Box testing method. The construction of an online ordering website Ikebana Florist Shop can use it as a medium to promote the products it sells, so it can be known more widely